Leadership in healthcare : essential values and skills - Dye, Carson F. (Chicago, IL : Health Administration Press, a division of the Foundation of the American College of Healthcare Executives, 2023)
"Today's healthcare leaders face constant challenge and change. Even as they cope with a rapidly evolving environment, they also must overcome existing obstacles inherent to running multifaceted operations. A solid value system must anchor leaders as they navigate all these daily challenges"--
The leadership imperative -- A review of academic leadership theories and concepts -- Is the popular leadership literature worthless? -- The values-based definition -- The senior leader challenge -- Respect as the foundation of leadership -- Ethics and integrity -- Interpersonal connection -- Servant leadership -- Desire to make a change -- Commitment -- Emotional intelligence -- Cooperation and sharing -- Cohesiveness and collaboration -- Trust -- Conflict management -- Assessing team values -- Evaluating team effectiveness -- Self-evaluation at all career stages -- Inclusive leadership / Carla Jackie Sampson -- Physician leadership issues / Margot Savoy -- Humans working with humans to heal humans / Katherine A. Meese and David A. Rogers -- Leadership matters : for healthcare's present and future / Patrick D. Shay -- Post-COVID leadership.
Includes bibliographical references and index.
Keywords: Health Services Administration; Leadership; Administrative Personnel; Print books